Get Help From Experts in Data Science and Mathematics
ePortfolios |STEM Gender Equality | ZOOM | Slack | Spreading Mathematical Happiness

You can support MathsGee with your DONATION

0 like 0 dislike
24 views
Let $u(n) = -n^3 - n^2$. Let $e(c) = -2c^3 + c$. Let $l(j) = -118e(j) + 54u(j)$. What is the derivative of $ l(a)$?
by Diamond (53,882 points) | 24 views

1 Answer

0 like 0 dislike
First find e(j) and u(j) ,

e(j) = -2j^3 + j

u(j)= -j^3  - j^2

Therefore l(j)= -118(-2j^3 +j) + 54(-j^3-j^2)

                  = 236j^3 - 118j -54j^3 - 54j^2

                   = 184j^3 - 54j^2 - 118j

  l(a) = 184a^3 - 54a^2 - 118a

dl/da = 552a^2 -102a - 118
by Diamond (40,360 points)

Related questions

Welcome to MathsGee Q&A Bank, Africa’s largest personalized FREE Study Help network that helps people find answers to problems and connect with experts for improved outcomes.


Get help from experts - simply ask your question


You can Support MathsGee with your DONATION

Enter your email address:

13,102 questions
10,327 answers
101 comments
11,185 users